2022
DOI: 10.3390/healthcare10071182
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Use of the Suppression Head Impulse Paradigm in Patients with Vestibulopathy: A Systematic Review

Abstract: Background: This review aims to explore the potential clinical application of the suppression head impulse paradigm (SHIMP) in patients with unilateral and bilateral vestibulopathy. Methods: An electronic search was conducted by two independent reviewers in the following databases: Embase, MEDLINE (PubMed), and Scopus. The screening of titles, abstracts, and full texts and data extraction were undertaken independently by pairs of reviewers. The included studies were quality appraised using a modified version o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Another limitation is the absence of an instrumental evaluation of the vestibular reflexes’ functions [ 55 , 56 ], but, even in a probable absence of specific vestibular damage for the enrolled sample, VR was not expected to lead to improvements in vestibular reflexes. In fact, it seems rather to act as a facilitator for improving a compensation strategy based on the enhancement of the vestibular network and sensory–motor integration for managing a correct trade-off between stability and advancement during gait.…”
Section: Limitationsmentioning
confidence: 99%
“…Another limitation is the absence of an instrumental evaluation of the vestibular reflexes’ functions [ 55 , 56 ], but, even in a probable absence of specific vestibular damage for the enrolled sample, VR was not expected to lead to improvements in vestibular reflexes. In fact, it seems rather to act as a facilitator for improving a compensation strategy based on the enhancement of the vestibular network and sensory–motor integration for managing a correct trade-off between stability and advancement during gait.…”
Section: Limitationsmentioning
confidence: 99%
“…24,25 Emerging evidence shows high sensitivity and specificity for measuring vestibular weakness, of more than 87 per cent and more than 83 per cent respectively, especially when paired with the video head impulse test. 26…”
Section: Video Head Impulse Testmentioning
confidence: 99%
“…In a recent review of literature ( 13 ) on SHIMP, it was observed that the test not only complemented the HIMP but also yielded better values on the VOR gain as contaminating covert saccades contributing to VOR gain are far less. PSV and the percentage of saccades indicate compensating vestibular function which are useful to glean an idea about central pathways that govern the suppression mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…PSV and the percentage of saccades indicate compensating vestibular function which are useful to glean an idea about central pathways that govern the suppression mechanism. The sensitivity and specificity are postulated to be nearly 100% to diagnose a vestibular weakness ( 13 ). SHIMP behaves differently in uncompensated and compensated vestibular deficits and may be useful to plan a rehabilitation program.…”
Section: Introductionmentioning
confidence: 99%